2017
DOI: 10.5897/ajb2016.15831
|View full text |Cite
|
Sign up to set email alerts
|

An improved protocol for in vitro propagation of the medicinal plant Mimosa pudica L.

Abstract: This work aimed to develop a protocol for the in vitro establishment, multiplication, rooting and ex vitro acclimatization of Mimosa pudica L., a species used in folk medicine and with pharmacological activity. Aseptic cultures were established from seeds inoculated in MS medium, without growth regulators, followed by an in vitro stabilization phase in culture medium supplemented with 2.22 μM BAP. The cultures were transferred to MS medium supplemented with different cytokinins, combined or not with an auxin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
2
2
1
Order By: Relevance
“…Above all, MS basal medium fortified with 17.6 μM KIN (Figure 3A) was selected as the best media for shoot multiplication of M. pudica due to the satisfactory shoot number and shoot length, a moderate amount of leaves with low basal callus formation. Consistent with the previous observation by Bianchetti et al (2017), the highest number of shoots recorded in 5 μM BAP was 5 shoots/explant, which was just marginally higher than those in the current study (4.87 shoots/explant in 35.2 μM KIN). It was also reported that increasing BAP concentration hindered shoot number and elongation, with plantlets reaching an average height of 2.5 cm, which was lower than the shoot length achieved in this study, which was over 3 cm.…”
Section: Shoot Multiplication Of M Pudica In Response To Different Pl...supporting
confidence: 93%
See 2 more Smart Citations
“…Above all, MS basal medium fortified with 17.6 μM KIN (Figure 3A) was selected as the best media for shoot multiplication of M. pudica due to the satisfactory shoot number and shoot length, a moderate amount of leaves with low basal callus formation. Consistent with the previous observation by Bianchetti et al (2017), the highest number of shoots recorded in 5 μM BAP was 5 shoots/explant, which was just marginally higher than those in the current study (4.87 shoots/explant in 35.2 μM KIN). It was also reported that increasing BAP concentration hindered shoot number and elongation, with plantlets reaching an average height of 2.5 cm, which was lower than the shoot length achieved in this study, which was over 3 cm.…”
Section: Shoot Multiplication Of M Pudica In Response To Different Pl...supporting
confidence: 93%
“…In general, the medium composition is one of the many factors that influence the success of an in vitro micropropagation protocol. The result from the most recent micropropagation study of M. pudica by Bianchetti et al (2017) in the germination part was not reproducible in this present study. To investigate this issue, other germination media components not addressed in the previous study, such as the type and strength of the basal medium and sucrose concentration, were assessed to establish a reproducible in vitro germination media for M. pudica seeds.…”
Section: Introductioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Plant tissue culture is the most popular method of ex-situ conservation strategy, which is user-friendly, low-cost; requires less space, energy and advanced tools. A few attempts have been tried to develop a tissue culture protocol for M. pudica using nodal explants and shoot tips as explants (Gharyal and Maheshwari 1982;Hassan et al 2010;Ramesh et al 2013, Bianchetti et al 2017 and hardened the plantlets as well. All the described protocols are similar to shoot multiplication methods and direct organogenesis protocol for the plant has been not reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…This auxin is widely used to induce rooting in shoots of woody legumes, such as Abrus precatorius (Biswas et al 2007), Bauhinia racemosa (Rajanna et al 2011), Cassia angustifolia (Siddique et al 2015), Dalbergia latifolia (Gulati and Jaiwal 1996;Manikandan et al 2017;Swamy et al 1992), D. retusa (Valverde-Cerdas andAlvarado-Guzmán 2004), D. sissoo (Ali et al 2012;Rehman et al 2012;Singh et al 2002), Pithecellobium dulce (Goyal et al 2012), and Pterocarpus santalinum (Prakash et al 2006). However, in some tree species, such as Alnus glutinosa (San José et al 2012) and Mimosa pudica (Bianchetti et al 2017), optimal in vitro rooting has been shown without the addition of auxins, which also promoted the development of secondary roots and the formation of plants suitable for transplant, acclimatization and greenhouse culture. The rooting of D. congestiflora shoots coincided with this response, suggesting that rooting was related to the auxin concentration of tissues.…”
mentioning
confidence: 99%